2015
DOI: 10.1185/03007995.2015.1016604
|View full text |Cite
|
Sign up to set email alerts
|

Critical analysis of common canister programs: a review of cross-functional considerations and health system economics

Abstract: Respiratory inhalers constitute a large percentage of hospital pharmacy expenditures. Metered-dose inhaler (MDI) canisters usually contain enough medication to last 2 to 4 weeks, while the average hospital stay for acute hospitalizations of respiratory illnesses is only 4-5 days. Hospital pharmacies are often unable to operationalize relabeling of inhalers at discharge to meet regulatory requirements. This dilemma produces drug wastage. The common canister (CC) approach is a method some hospitals implemented i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…A more recent assessment by another health system reported 90% of doses remaining unused, which correlated with the average LOS 6 . Our own internal evaluation of inhaler waste which was previously reported suggested a similar level of wasted doses (89%) and supports these assessments 7 . We additionally evaluated potential tiotropium (Spiriva Handihaler) waste more specifically since annual system costs exceeded $500,000 for this inhaler alone.…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…A more recent assessment by another health system reported 90% of doses remaining unused, which correlated with the average LOS 6 . Our own internal evaluation of inhaler waste which was previously reported suggested a similar level of wasted doses (89%) and supports these assessments 7 . We additionally evaluated potential tiotropium (Spiriva Handihaler) waste more specifically since annual system costs exceeded $500,000 for this inhaler alone.…”
Section: Introductionsupporting
confidence: 88%
“…This was also successful in significantly reducing the number of inhalers stocked on formulary; however, lost inhalers and wasted doses were still very prevalent as stated previously despite being able to increasingly utilize the institutional size inhalers provided by GSK. Another option that many hospitals have entertained to curb inhaler costs and minimize waste is by instituting common canister (CC) protocols and although these can be successful they do require close attention to detail as it relates to infection control issues as well as associated processes to be sure certain patient populations are excluded 7 . Despite implementing the system-approved preferred inhaler therapeutic interchange in 2012, three urban community hospitals in our health system still found inhaler costs and waste to be unacceptable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, further studies are required to determine the overall safety of shared canister therapy during mechanical ventilation, especially in other patient populations (eg, immune suppressed individuals) and non-ICU settings. 33 In this era of increasing antimicrobial resistance, an alternative approach would be to have smaller dose single-patient MDIs for hospital use.…”
Section: Discussionmentioning
confidence: 99%
“…There is weak evidence that the common canister protocol practiced in some hospitals can lead to cross-contamination. [ 209 ] In contrast, a recent study revealed that common canister protocol resulted in significant cost savings with similar rates of ventilator-associated pneumonia, mortality, as well as hospital length of stay, compared to single-patient pMDI. [ 210 ] Accordingly, each hospital should evaluate the risk–benefit ratio before following a common canister protocol.…”
Section: Aerosol Therapy At Home: Education and Cleaningmentioning
confidence: 99%